INTEGRATION OF ARTIFICIAL INTELLIGENCE IN THE SUPPLY CHAIN MANAGEMENT: INTEGRATION OF ARTIFICIAL INTELLIGENCE IN THE SUPPLY CHAIN MANAGEMENT - Stoyanov, Svetlozar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The suggested research aims to present a short and general overview of the integration of artificial intelligence in the supply chain management.